Between Promise and Peril: Blue Economy Development and Maritime Security in Africa-a Critical Review - Issa Ahmed; Abubakar Muhammad Jibril; Lukuba Machibya; Lamin Saidyjeng; Alkali Jallow; Peseo Lao Pio (CV. Sakura Digital Nusantara, 2026)
Purpose – This paper examines the relationship between blue economy development, maritime security, and governance in Africa, with a focus on the Gulf of Guinea and the Horn of Africa. It highlights how maritime insecurity affects key sectors such as fisheries, maritime transport, offshore energy, and coastal tourism. Design/methodology/approach – The study applies a comparative regional approach using peer-reviewed literature and policy reports published between 2000–2025. The analysis focuses on issues of piracy, maritime terrorism, smuggling, and trafficking, as well as governance responses in Africa’s major maritime regions. Findings/Results – The findings indicate that maritime insecurity creates significant economic and social costs for blue economy sectors through higher risks, disrupted trade routes, and livelihood instability. Although regional cooperation and maritime governance frameworks have expanded, their effectiveness is limited by legal fragmentation, unequal institutional capacity, and weak maritime monitoring systems. In addition, factors such as IUU fishing, youth unemployment, coastal marginalization, and state fragility continue to drive insecurity. Originality/Value – The study concludes that sustainable blue economy development depends on integrated governance that combines maritime security, legal reform, and development policy. The paper emphasizes that maritime security should not only be understood as an enforcement issue, but also as a governance and human security challenge linked to broader socio-economic conditions.